Sociodemographic, lifestyle and metabolic predictors of all-cause mortality in a cohort of community-dwelling population: an 18-year follow-up of the North West Adelaide Health Study - Melaku, Yohannes Adama (BMJ Open, 2019)
INTRODUCTION: Studies examining potential factors of all-cause mortality comprehensively at community level are rare. Using long-term community-based follow-up study, we examined the association of sociodemographic and behavioural characteristics, metabolic and chronic conditions, and medication and health service utilisation with all-cause mortality. METHODS: We followed 4056 participants, aged 18–90 years, for 18 years in the North West Adelaide Health Study (NWAHS). Mortality data were obtained from South Australian (SA) public hospitals and registries including SA births, deaths and marriages, the National Death Index and the NWAHS follow-up. Predictors of all-cause mortality were explored using Cox proportional hazard model, adjusting for potential confounders. We performed subgroup analyses by sex and age. RESULTS: Mean (SD) age at baseline was 50.4 (16.4) years. Less than half (47.8%) of the participants were men. A total of 64 689.7 person-years from 4033 participants with 18.7 years of follow-up were generated. The median follow-up time was 17.7 years; 614 deaths were recorded. The overall crude death rate was 9.6 (95% CI 8.9 to 10.4) per 1000 person-years. After adjusting for potential confounders, a reduced risk of mortality was significantly associated with being separated or divorced, being in the highest Socioeconomic Indexes for Areas quintile, engaging in moderate exercise, being overweight (body mass index: 25.0–29.9 kg/m(2)) and per 10% increase in per cent predicted forced expiratory volume in 1 s. We found that the most important predictors of all-cause mortality were sociodemographic and behavioural characteristics. Sociodemographic factors were more important predictors of all-cause mortality in young age bracket compared with older people. CONCLUSIONS: Socioeconomic factors were found to be the most important predictors of all-cause mortality. The study highlights the need to address the social inequalities and strengthen behavioural interventions for different subgroups of population to prevent premature deaths.